PELATIHAN PEMANFAATAN SAMPAH DAUN KERING DAN SAMPAH SISA MAKANAN MENJADI PUPUK ORGANIK CAIR DALAM MEWUJUDKAN GREEN HOUSE DI METLAND TAMBUN CLUSTER FONTANIA - Fata Nidaul KHASANAH; Syahbaniar ROFIAH; Didik SETIYADI; Rizal Nanda REYNALDI (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2020)
Settlements are one of the sources of contributors in the growing number of garbage. Handling waste done well in processing can provide benefits at once can reduce the buildup of existing garbage volumes. The purpose of this training is how to utilize dried leaf garbage and leftover waste food to be processed into liquid organic fertilizer that can provide benefits for the environment so as to preserve plants around the settlement to To a beautiful, fresh and green settlement so it is realized